Vaginal assisted laparoscopic sacrocervicopexy with anterior colpotomy (VALSAC): technique and mean 20 months outcomes - O. Sevket; T. Takmaz; A.C. Sevket; A. Toprak; P. Ozcan (Clinical and Experimental Obstetrics & Gynecology)
The main purpose of our study is to evaluate the efficacy and safety of vaginal assisted laparoscopic sacrocervicopexy with anterior colpotomy (VALSAC) for apical pelvic organ prolapse. We retrospectively reviewed the results of twenty-three women with stage III and IV prolapse treated with VALSAC between April 2017 and June 2019. With a mean follow-up of 20 months, apical pelvic organ prolapse was cured in 95.7 % of patients. There was no complication in terms of mesh exposure, persistent pain, hematoma, infection. The mean pre- and post-operative POP-Q scores were, for the Aa point, 1.61 ± 1.82 cm and -1.96 ± 0.87 cm (p < 0.01), for the C point, 2.87 ± 1.6 cm and -5.26 ± 1.86 cm (p < 0.01) for the Ap point, -1.43 ± 0.89 cm and -2.09 ± 0.59 cm (p < 0.01). VALSAC is a promising minimally invasive technique for pelvic floor reconstruction that appears to provide good outcomes. Content: The main purpose of our study is to evaluate the efficacy and safety of vaginal assisted laparoscopic sacrocervicopexy with anterior colpotomy (VALSAC) for apical pelvic organ prolapse.